FREQUENCY OF WOUND DEHISCENCE IN POSTERIOR SAGITTAL ANORECTOPLASTY IN CHILDREN (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To identify independent risk factors, assess the clinical role of the occurrence of wound dehiscence after PSARP in pediatric patients with anorectal malformations and to determine the frequency.Material and Method: The study was conducted as a prospective cohort study in a tertiary surgical center specializing in children's surgery from January 2023 to December 2025. The children enrolled were those who were ≤12 years old at PSARP or staged PSARP. Wound dehiscence was partial or complete separation of the midline perineal wound, necessitating clinical intervention. A p-value of